Expression profile and gap-junctional transfer of microRNAs in the bovine cumulus-oocyte complex - Six, R.; Benedetti, C.; Fan, Y.; Guan, X.; Gansemans, Y.; Hedia, Mohamed; Bogado Pascottini, O.; Pavani, K. C.; Van Nieuwerburgh, F.; Deforce, D.; Smits, K.; Van Soom, A.; et al. (Frontiers in Cell and Developmental Biology, 2024)
MicroRNAs (miRNA) are important regulators of oocyte maturation, playing a key role in modulating gene expression both in a temporal-and spatial-specific manner. These small non-coding RNAs are involved in important processes during oocyte maturation, acting as messengers between the oocyte and its surrounding cumulus cells. Despite its significance, the bidirectional communication mechanism is still unknown. To test miRNA communication between oocyte and surrounding cumulus cells through the gap junctions the gap junctions were either blocked with carbenoxolone or not. MiRNA sequencing of oocytes at 1, 6, and 22 hours of in vitro maturation was then performed. Among the differentially expressed miRNAs, bta-miR-21-5p, a regulator of cumulus cell viability and oocyte maturation, was the only previously known miRNA. Furthermore, by labeling a bta-miR-21-5p mimic with FAM, crossing of this miRNA through the gap junctions within the cumulus-oocyte complex could be visualized and internalization in the oocyte was confirmed by RT-qPCR. In conclusion, this study provides, for the first time, evidence that miRNA communication within the bovine cumulus-oocyte complex is enabled through the gap junctional network.